Noise Modeling - Mohd Amir Nazmi B Romli, Mohd Amir Nazmi (Universiti Teknologi Petronas, 2011)
From this paper, there will be three studies that have been conducted. There are (1) Fan interaction noise (2) Modeling Noise for HWAT rotor, (3) Modeling near and far field Noise. In first research , a 3-D, unsteady, Reynolds-averaged Navier-Stokes (RANS) CFD code coupled to an acoustic calculation is used to predict the contribution of the exit guide vanes to tonal fan noise downstream. The configuration investigated is that corresponding to the NASA Source Diagnostic Test (SDT) 22-in fan rig. In this chosen configuration, there are 22 rotor blades and 54 stator blades. The stators are located 2.5 tip chords downstream of the rotor trailing edge. The RANS computations are used to obtain the spectra of the unsteady surface pressure on the exit guide vanes. Comparison of the computed sound power level at the exhaust plane with experiment show good agreement at the cut-on circumferential mode. The results and the validation from this investigation validate the use of the CFD code along with the acoustic model for downstream fan noise predictions. Besides that, for second research the paper demonstrates a computational methodology for the noise prediction of an horizontal axis wind turbine (HAWT) rotor in time domain. The aeroacoustic modeling is based on the Ffowcs Williams and Hawkings equation considering only the surface monopole and dipole noise sources.The aerodynamic analysis uses a two-dimensional low-order panel method combined for the calculation of the blade pressure distribution, obtaining satisfactory agreement with experimental data. Sound pressure level contours occur via Fourier transformations, while the directivity for a single frequency source is also examined. The final research is regarding the computational method to compute the near and far field noise of the vehicle. As aerodynamic component of noise is one of major contribution to the noise level that effect the environment, the near field flow time dependent pressure history in the flow is generated using computational fluid dynamic. The Numerical scheme is developed from acoustic far field noise predictions which use the near field solution as input to Kirchhoff formulation.